Confessions of guilt: from torture to Miranda and beyond - Thomas, George C. (Oxford Univ. Press, 2012)
How did the United States, a nation known for protecting the "right to remain silent" become notorious for condoning and using controversial tactics like water boarding and extraordinary rendition to extract information? What forces determine the laws that define acceptable interrogation techniques and how do they shift so quickly from one extreme to another? In Confessions of Guilt, esteemed scholars George C. Thomas III and Richard A. Leo tell the story of how, over the centuries, the law of interrogation has moved from indifference about extreme force to concern over the slightest pressure